ENERGY EFFICIENCY PREDICTION BASED ON THE INTEGRATION OF PHOTOVOLTAIC SOLAR PANELS AS A DOUBLE SKIN FACADE IN EXISTING OFFICE BUILDINGS - Marouane Samir Guedouh; Hocine Sami Belmahdi (International Journal of Innovative Technologies in Social Science, 2025)
The objective of this research is to address issues related to the energy efficiency of administrative buildings. The energy renovation of buildings using photovoltaic systems as a second skin offers several advantages, including: The integration of solar PV systems into the building’s exterior envelope appears effective and promising for the future facades of existing administrative buildings, where these systems offer renewable energy production and improving the building’s interior comfort. To adjust the energy efficiency of office buildings, this study provides a step-by-step process for predicting the energy efficiency of integrating these PV systems. The main steps of the approach are: (1) studying the environment and thermal potential of buildings using a "Testo 865" thermal camera and a "Testo 830-T2" infrared thermometer; (2) proposing the double-skin facade (DSF) system; (3) calculating the efficiency of these PV systems by applying a calculation formula for PV system production. The results demonstrated that the maximum efficiency of the PV systems, depending on the cases of the studied buildings, can reach up to 32% of the total annual electrical consumption. The PV system can become a second skin for the existing facade, helping to minimize energy consumption while improving the thermal performance and appearance of existing administrative buildings.